Uitrol van de functionaliteitseconomie in het Brussels Hoofdstedelijk Gewest: een stand van zaken - Coline Ruwet; François Lohest; Roxane De Hoe; Kevin Maréchal; Coralie Muylaert; Géraldine Thiry; Philippe Roman (Brussels Studies, 2023)
Since 2016, the Brussels-Capital Region (BCR) has been committed to putting transition at the heart of its economic strategy. Among the promising economic models is the functional economy (FE), whereby the sale of the use of a product is substituted for the sale of the product itself. It has several virtues in terms of sustainability. By retaining ownership of goods, companies would be encouraged to choose sustainable products. Making the same product available to different users would limit the quantities produced. The FE also serves as a catalyst for the local presence of production and consumption systems. Yet, in BCR, the FE model remains little known, poorly understood and is having trouble unfolding. This article – which is the result of four years of research on the FE in BCR – has three objectives: 1) it provides an original overview of the current state of the FE in BCR and the diversity of needs which the FE could meet; 2) it analyses the institutional measures for supporting the FE in BCR; and 3) it questions the balance between the institutional measures for supporting a sustainable economy in BCR and the expansion of the FE in the region. This exploratory study shows that the FE still has only a marginal presence in institutional terms and in the economic fabric of Brussels. It would therefore seem appropriate to make more room for the FE model, by creating areas for economic stakeholders to experiment with the model and evaluate its effects in terms of sustainability, build a common vision and determine the directions for its expansion.